Psychotherapeutic Approaches for Enhancing Perinatal Mental Health - Anupa Devi Kairy; Deepika Chamoli Shahi; Rita Kumar (International Journal of Behavioral Sciences, 2024)
Pregnancy is a life turning event in a woman's life. Many women during pregnancy and after the birth of the child face mental health issues like anxiety, depression, and stress due to varied reasons. If not addressed properly, these can affect the mother-child bond, the lady's relationship with the entire family, and the child's cognitive and emotional development. As per WHO, “Globally about 10% of pregnant women and 13% of postnatal women experience a mental health disorder, primarily depression. In developing countries, the rate is even higher, i.e. 15.6% during pregnancy and 19.8% after childbirth. In severe cases mothers’ suffering might be so severe that they may even commit suicide. Psychotherapy, sometimes referred to as talk therapy, is one of several therapeutic modalities that a psychotherapist uses to assist clients in recognizing and addressing the negative feelings, ideas, and behaviors that are causing them distress. Researchers throughout the world have proved that maternal mental health affects the health of the unborn child and thus the entire family is affected. Therefore, there is a need to find out an effective psychotherapeutic technique to deal with perinatal mental health issues. This study aims to find out the efficacy of psychotherapies during the perinatal period and the most effective psychotherapeutic technique in dealing with perinatal mental health. The purposive sample method was used to choose five pregnant women, and the interview technique was used to collect data over the phone. CBT in combination with the progressive relaxation technique was found to be the most effective therapy in dealing with mental health issues of women in the perinatal period.
Keywords: Maternal health; perinatal mental health; postnatal depression; progressive relaxation; psychotherapeutic techniques